The Implementation of Merdeka Curriculum on Historical Subject at SMA Negeri 3 Jember - Setyawati, Laily; Umamah, Nurul; Sumardi, Sumardi; Marjono, Marjono (History Education, University of Jember, 2023)
The occurrence of learning loss during the Covid-19 pandemic resulted in decreasing students' knowledge & skill. In order to overcome the learning loss, the Ministry of Education and Culture issued a new breakthrough namely the merdeka Curriculum. The research's aim is to examine in depth (1) availability of facilities, infrastructure & human resources; (2) The implementation of Process and assessment standards of merdeka. The research method used is qualitative. Data collection techniques used are; observation, interview, and documentation. Data analysis consists of 3 stages: Data reduction, Data display and Conclusion & verification. The results of this research ; (1) The facilities are good & complete. The infrastructure has good condition, but it's not complete; (2) It has quality human resources;(3) The process standards are in accordance with planning, implementation, and assessment. The planning has not been changed while the implementation & assessment are different from the planning used. The assessment standards are carried out fairly, objectively and educatively. The assessment used is formative assessment. Keywords: Independent curriculum, History Lesson, Facilities & Infrastructure, Process Standards, Assessment Standards